2007
DOI: 10.1089/neu.2007.0302
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Myelin Pathology Differs following Contusion and Transection Spinal Cord Injury

Abstract: Demyelination is a prominent feature of spinal cord injury (SCI) and is followed by incomplete remyelination, which may contribute to physiological impairment. Demyelination has been documented in several species including humans, but the extent of demyelination and its functional consequence remain unknown. In this report, we document and compare the extent of tissue pathology, white matter apoptosis, demyelination, and remyelination 2 months following injury in rat contusion and transection models of SCI. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 59 publications
3
56
0
Order By: Relevance
“…A further study reported that in complete spinal cord transection rats, locomotor recovery after transplantation with both OPCs and human ESC-derived motor neuron progenitor cells was significantly greater than after treatment with either cell type alone [49]. Given that the application of stem cells and their progenitors for transplantation is currently in its infancy, and that SCI pathology differs between contusion and transection [50], these findings indicate that neural cells in an appropriate lineage should be transplanted according to the degree and/or type of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…A further study reported that in complete spinal cord transection rats, locomotor recovery after transplantation with both OPCs and human ESC-derived motor neuron progenitor cells was significantly greater than after treatment with either cell type alone [49]. Given that the application of stem cells and their progenitors for transplantation is currently in its infancy, and that SCI pathology differs between contusion and transection [50], these findings indicate that neural cells in an appropriate lineage should be transplanted according to the degree and/or type of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…10 The biology of contusion also appears to be different from hemisection or transection models. 11 Iseda, et al compared the effect of intraspinal chondroitinase ABC injection on neuroregeneration separately in hemisection and contusion models. 4 Axonal regeneration was observed in the neuronal bridge in hemisection but not the contusion SCI group.…”
Section: Introductionmentioning
confidence: 99%
“…31 Furthermore, the level of injury can affect pathophysiological events, especially when neurons are evaluated after injury, and the amount of apoptosis after axotomy depends on the distance of the injured site from the cell body. 32 Moreover, in compression/ contusion model of injury, the applied force and duration of compression are the most effective factors on the severity of injury.…”
Section: Methods Of Allocation To Treatmentmentioning
confidence: 99%